2008
DOI: 10.1007/s00128-008-9544-0
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticides in the Soil in Linfen, China

Abstract: Eighteen organochlorine pesticides (OCPs) in air particulate matter (PM) samples collected from 20 sites in Beijing, China in 2005 and 2006 were analyzed to determine the composition, spatial distribution and sources. Total OCPs of PM 2.5 and PM 10 ranged from 32.59 pg m −3 to 9232.31 pg m −3 and 80.96 pg m −3 to 9434.97 pg m −3 , respectively, categorized as heavier pollution compared to other cities of China. Among six kinds of functional zones involved, commercial areas and industrial centers were heavily p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…22 A ratio ratio < 1 indicates relatively recent exposure to the parent DDT. 14 In the present study, the ratios of (p,p 0 -DDE + p,p 0 -DDD)/p,p 0 -DDT were <1 in all samples, indicating that the contamination occurred in recent years. Given the above discussion, it can be concluded that new input sources of DDTs may be present in this region, and dicofol and anti-fouling paint were identified as probable culprits.…”
Section: Sources Of Ocpssupporting
confidence: 42%
See 1 more Smart Citation
“…22 A ratio ratio < 1 indicates relatively recent exposure to the parent DDT. 14 In the present study, the ratios of (p,p 0 -DDE + p,p 0 -DDD)/p,p 0 -DDT were <1 in all samples, indicating that the contamination occurred in recent years. Given the above discussion, it can be concluded that new input sources of DDTs may be present in this region, and dicofol and anti-fouling paint were identified as probable culprits.…”
Section: Sources Of Ocpssupporting
confidence: 42%
“…DDT and HCH concentrations in soil in Shenzhen were slightly higher than or comparable with those in agricultural soils of other locations in China. [12][13][14] However, the detection rates of DDTs were below 10% (Table S1 †), which indicated accidental occurrence of these compounds in Shenzhen. That the current DDT pollution in the soil of Shenzhen was not severe may be due to the agricultural land decreasing sharply with the urbanization over the past 30 years.…”
Section: Occurrence Of Ocpsmentioning
confidence: 99%
“…The ratio of ( p,p ′-DDE + p, p ′-DDD/ p,p ′-DDT) is often used as an index for assessing the residence time of p,p ′-DDT in the environmental. A value >1.0 indicates that the application was performed in the past, and a value <1.0 indicates a relatively recent application (Cheng et al 2008). In this study, this ratio p,p ′-DDE/ p,p -DDT was 3.3 > 1.0, which is an indication of past exposure to DDT.…”
Section: Discussionmentioning
confidence: 99%